What matters for sustainability and climate change actions in developing countries: A stimulus–organism–behavior– consequence (SOBC) perspective - Tan, Fuqiang; Luqman, Rabia; Asmi, Fahad; Zhou, Rongting; Anwar, Muhammad Azfar (Frontiers in Environmental Science, 2023)
Sustainable behaviors demand wielding communication strategies in social and political spheres for public understanding of scientific issues like climate change and the severe consequences of deteriorating environmental quality. Reliable information can improve public understanding of science and enhance public support for climate change actions at social and political levels. The study strives to examine the socio-political and psychological factors which affect climate change actions based on the stimulus-organism-behaviour-consequences paradigm. The study further categorizes sustainable behavior into mitigation and adaptation strategies to tap behavioral consequences with the moderating effects of information literacy and a regulative environment. Empirical findings demonstrate interesting associations between socio-political and psychological factors. Significant effects were observed for environmental quality and belief in climate change in explaining pro-environmental behavior. The study reveals that people are more prone to mitigation than adaptation strategies to ensure sustainability. The study recommends better communication strategies to empower those already engaged in mitigating climate change and encourage those still struggling to adapt to climate change actions.